2019
DOI: 10.1038/s41598-019-43838-8
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Iranian Propolis on Glucose Metabolism, Lipid Profile, Insulin Resistance, Renal Function and Inflammatory Biomarkers in Patients with Type 2 Diabetes Mellitus: A Randomized Double-Blind Clinical Trial

Abstract: Propolis is a natural product with many biological properties including hypoglycemic activity and modulating lipid profile. The present study was designed to evaluate the effect of Iranian propolis extract on glucose metabolism, Lipid profile, Insulin resistance, renal and liver function as well as inflammatory biomarkers in patients with type 2 diabetes mellitus (T2DM). A double-blind, placebo-controlled clinical trial was conducted. The duration of the study lasted 90 days. Patients with T2DM were recruited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
108
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(148 citation statements)
references
References 70 publications
(80 reference statements)
3
108
1
3
Order By: Relevance
“…In the present study, propolis supplementation alone and in combination with melatonin was able to reduce the levels of in ammatory factors. In line with our study, propolis (1000 mg daily) for 12 weeks in diabetic patients was able to signi cantly reduce CRP and TNF-α levels (41). Other clinical trials have shown that propolis at doses of 830 mg to 1,500 mg in some chronic disease can signi cantly reduce the levels of in ammatory factors (20,42,43), while lower doses of propolis did not effect on the in ammation levels (44).…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, propolis supplementation alone and in combination with melatonin was able to reduce the levels of in ammatory factors. In line with our study, propolis (1000 mg daily) for 12 weeks in diabetic patients was able to signi cantly reduce CRP and TNF-α levels (41). Other clinical trials have shown that propolis at doses of 830 mg to 1,500 mg in some chronic disease can signi cantly reduce the levels of in ammatory factors (20,42,43), while lower doses of propolis did not effect on the in ammation levels (44).…”
Section: Discussionsupporting
confidence: 90%
“…The current paper provides strong support for propolis being effective as an anti-inflammatory complex. Propolis has been studied as an immunomodulatory agent in a number of sizeable trials, and its safety in high doses is good [ 9 , 10 , 11 , 12 , 13 ]. There had been no studies examining whether or not the components in propolis are absorbed.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent paper, we studied several types of propolis for their effects on the metabolic response of THP-1 cells to treatment with lipopolysaccharide (LPS), and for one sample from Cameroon, which inhibited cytokine release, we studied the metabolomics of the immune response and found a clear effect of the propolis in inhibiting purine nucleotide phosphorylase [ 8 ]. In addition, there have been some quite extensive trials of propolis in humans aimed at affecting the immune response [ 9 , 10 , 11 , 12 , 13 ]. The commonly available propolis supplements, such as glycerol-based tinctures, lozenges, and capsules, are mainly based on temperate propolis such as that collected by bees in the UK.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported that propolis has beneficial effects on reducing post prandial blood glucose, inflammatory cytokines, insulin resistance and serum insulin. Furthermore, the study found that propolis can also prevent liver and renal dysfunction in patients with Type 2 diabetes mellitus [ 18 ].…”
Section: Introductionmentioning
confidence: 99%